Transformations in the Canadian Youth Justice System. Creation of Statutes and the Judicial Waiver in Quebec - Pinero, Veronica B. (Université d'Ottawa / University of Ottawa, 2013)
The objectives of this thesis were to observe how the Canadian youth justice system has dealt with the regulation of the transfer of young offenders to the adult court and how the Canadian statutes have regulated the imposition of adult offences for young offenders. For this, I drew a distinction between two levels of observation: first, I observed the process of "creation of statutes" by the political system. Second, I observed the process of "understanding and interpretation of statutes" by the judicial system. The notion of "political system" includes the legislation enacted by Parliament, parliamentary debates, and reports published by the Government of Canada. The notion of "judicial system" includes the decisions of the Montreal Youth Court. For the first level of observation ("creation of statutes"), I observed and analyzed the work of the political system for the period 1842 to 2012. Starting in 1857, many statutes regulated different aspects of the criminal law system as it applied to young people. The first statute to deal with youth offenders comprehensively and different from adult offenders was the Juvenile Delinquents Act (1908); this statute was replaced by the Young Offenders Act (1982). The current statute is the Youth Criminal Justice Act (2002). With regard to the Juvenile Delinquents Act (1908) and the Young Offenders Act (1982), I observed how the political system regulated the mechanism of transferring a young person to the adult court. This mechanism allowed the youth court to decide a question of jurisdiction: whether the young person would be processed and sentenced within the youth justice system, or whether the young person would be sent to the adult court for him to be dealt with and sentenced therein. With regard to the Youth Criminal Justice Act (2002), I observed how the political system has regulated the imposition of adult sentences by the youth court. This statute replaced the mechanism of transfer under the two previous statutes by the imposition of adult sentences within the youth justice system. For the second level of observation ("the understanding and interpretation of statutes"), I observed how the Montreal Youth Court had understood and interpreted the statutory provision that allowed the youth court to transfer a young person to the adult court for the young person to be dealt with and sentenced therein. My period of observation is from 1911 to 1995. I argue that both the political and the judicial systems have been strongly influenced by the theories of deterrence, denunciation, retribution, and rehabilitation. The influence that each theory has exercised on each system varies. The political system, originally focused on the rehabilitation of young people, has been slowly “contaminated” by the most punitive theories, such as deterrence and denunciation. This shift started in the 70’s and slowly increased over the years. Conversely, while the judicial system does not seem to have been originally influenced by the theories of rehabilitation, its focus has slowly shifted towards this objective as the primary goal of their intervention towards young offenders since the 70’s. However, the “successful rehabilitation” of a young person has become a goal in itself, where “unsuccessful offenders” have been transferred to the adult court and dealt with the adult punitive justice system.
Keywords: transfer to the adult court; imposition of adult sentences; youth criminal justice system; Canada; creation of laws; Montreal Youth Court; theories of punishment; rehabilitation; Quebec; understanding and interpretation of statutes